POLITIK HUKUM (LEGISLASI) HUKUM KELUARGA DI SAUDI ARABIA - Nurhayati, Agustina (Universitas Islam Negeri Raden Intan Lampung, 2014)
The legal system of Saudi Arabia is basedon Sharia, derived from the Qu'ran, the Sunnah andalso include Islamic scholarly consensus. Itsinterpretation by judges is influenced by the medievaltexts of the literalist Hanbali school ofIslamic jurisprudence. Laws relating to marriage,divorce, children and inheritance are not codified andfall within the general jurisdiction of the Sharia courts.Polygamy is permitted for men but is limited to fourwives at any one time. There is no minimum age formarriage in Saudi Arabia and with regard to the law ofinheritance, the Quran specifies that fixed portions ofthe deceased's estate must be left to the socalledQuranic heirs.